Extending the Use of Coal Beyond 2030, a Compromise Solution in the Case of Romania, to Ensure Energy Security - Dorobat, Leonard Magdalin; Turtureanu, Anca; Dobrescu, Codruța Mihaela (Journal of Danubian Studies and Research, 2022)
In the current geopolitical context, following the Russian invasion of Ukraine, the energy consequences are severe for almost all European countries, whether they are EU members or not. A blind energy policy pursued over the last 20–30 years by most EU countries has led to an over-reliance on a single source for gas and/or oil: Russia. Moreover, the hasty implementation of measures to shut down fossil fuel-fired power plants without finding viable alternatives in place has exacerbated this poisonous dependence on Russian gas sources. As a result, following the new geopolitical framework, Europe is forced to revert to an old source of energy, coal, at least for a certain period, revise its energy and environmental policy. Many countries such as Italy, Germany, Poland, the Czech Republic, etc. have already passed or intend to move to the reopening of coal mines and thermal power plants that use this source. Poland, which obtains about 75% of its energy from coal, initially set itself the goal of giving up this resource in 2049, but now this deadline will be "much more" postponed. Germany has kept its 2030 target for this goal, if all goes well. Considering all this and because Romania is not independent of the energy viewpoint, we consider that also in this case it is beneficial from the economic and energy security perspective to keep in operation the coal mines and the thermal power plants that use this raw material, beyond the horizon of 2050. This can be done by refurbishing mines and thermal power plants and by implementing efficient management, totally different from what has happened over the years so far. Only when the so-called clean, "renewable" or other energy sources with a soft environmental impact can cover the energy deficit can the use of fossil fuels and, especially, coal be safely abandoned.